2019
DOI: 10.3390/informatics6030029
|View full text |Cite
|
Sign up to set email alerts
|

Exhibiting Uncertainty: Visualizing Data Quality Indicators for Cultural Collections

Abstract: Uncertainty is a standard condition under which large parts of art-historical and curatorial knowledge creation and communication are operating. In contrast to standard levels of data quality in non-historical research domains, historical object and knowledge collections contain substantial amounts of uncertain, ambiguous, contested, or plainly missing data. Visualization approaches and interfaces to cultural collections have started to represent data quality and uncertainty metrics, yet all existing work is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
(62 reference statements)
0
25
0
Order By: Relevance
“…They found that fuzziness, location, value, arrangement, size, and transparency were rated as highly intuitive. The theory of visual semiotics of uncertainty [14] has inspired numerous applications of metaphoric uncertainty visualization from cultural collections [74] to educational reporting systems [75].…”
Section: Visual Semiotics Of Uncertaintymentioning
confidence: 99%
“…They found that fuzziness, location, value, arrangement, size, and transparency were rated as highly intuitive. The theory of visual semiotics of uncertainty [14] has inspired numerous applications of metaphoric uncertainty visualization from cultural collections [74] to educational reporting systems [75].…”
Section: Visual Semiotics Of Uncertaintymentioning
confidence: 99%
“…Law [67] reviewed website evaluation models and pointed out that in recent years, website audits have most frequently focused on content quality. On the other hand, Windhager et al [68] demonstrated that the quality of data and the quality of their visualisation were of significance in the presentation of large data sets.…”
Section: Research Into Website Qualitymentioning
confidence: 99%
“…Selection of an appropriate number of uncertainty levels is also of importance since discriminability of different degrees of uncertainty is impeded with the number of uncertainty degrees represented (Erev & Cohen, 1990). Windhager et al (2019) discuss the trade-off between the omission of uncertainty information at different levels leading to the deception of the recipients and visual complexity that overstrains the cognitive capacities of the recipients. In line with this, Correll et al (2018) showed that when using color scales to represent values or uncertainty, performance accuracy in an identification task is better with a discrete than with a continuous scale, indicating a trade-off between quantization error with using discrete scales of inherently continuous variables and perception error with continuous scales.…”
Section: Processing Visual Expressions Of Uncertaintymentioning
confidence: 99%